Comparative Study of Surface Treatment Procedures for Dental Implants - Bereczki, Alexandra; Ficzere, Péter (International Journal of Engineering and Management Sciences, 2025)
Nowadays, the most common type of implant in dentistry is a partial tooth replacement, such as a crown, or a complete tooth replacement. Today, many manufacturers offer implants made of a wide variety of materials and designs. These restorations must meet strict standards, one of the most stringent being surface roughness. Since proper bone-to-implant contact only occurs with adequate surface roughness, several methods are used to achieve the correct value. After reviewing the results of experiments carried out by several research groups, it is concluded that the surface roughness, the shape of the implant fixation screw, the shape of the thread and the thread elevation used to achieve the desired roughness together determine the success of the implantation. The average surface roughness required for osseointegration is considered to be optimal for values between 1 and 100 µm. In most cases, the surface roughness of commercially available dental prostheses is Ra 1-2 µm, but this can be modified by various grinding, acid etching and polishing processes to suit the application. Acid etching is a common technique for roughness reduction, which is the most effective in reducing surface roughness of dental restorative materials (mostly titanium alloys), thus bringing the roughness within the desired range. The result of acid etching is influenced by the concentration of acid, the temperature of the acid bath and the time spent in the acid. The acid used for the surface treatment is important and is most commonly sulphuric acid, hydrochloric acid or hydrogen fluoride (HF) and combinations of these. The study shows that the most optimal results are obtained with HF. Replacements are nowadays largely made by additive manufacturing, which allows for customised replacements and, due to dimensional accuracy, reduces the time and cost of post-processing, i.e. the surface treatment can be used to achieve the desired surface roughness and size at the same time. As a result, newer materials are being used for clinical prostheses and surface treatment should be applicable to all materials. The most optimal solution is a combination of grit blasting and acid etching. With this technology, the surface roughness for all materials reaches the optimum value of 1-100 µm, sometimes 1-2 µm, but can be further reduced below 1 µm by polishing. The study investigates the role of surface roughness, the surface roughness should only be reduced up to a certain value, approximately 0.5 µm, as smooth surfaces have limited or no potential for osseointegration.